State-of-the-art Survey of Data Hiding in ECG Signal - Velinov, Aleksandar; Stojanovic, Igor; Dimitrova, Vesna (My University, 2021)
With the development of new communication technologies, the number of biomedical data that is transmitted is constantly increasing. This is sensitive data and therefore it is very important to preserve privacy when transmitting it. For this purpose, techniques for data hiding in biomedical signals are used. This is a comprehensive survey of research papers that covers the latest techniques for data hiding in ECG signal and old techniques that are not covered by the latest surveys. We show an overview of the methodology, robustness, and imperceptibility of the techniques.